2017
DOI: 10.1002/zoo.21351
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of polycystic kidney disease and captive population viability in pygmy hippopotamus (Choeropsis liberiensis)

Abstract: Polycystic kidney disease (PKD) was previously diagnosed at necropsy in several pygmy hippopotami (Choeropsis liberiensis) from the Smithsonian National Zoo and Zoo Basel, suggesting a threat to the long-term viability of the captive population. We determined the incidence and demographics of PKD in the captive population historically; we tested if the condition is linked to pedigree; we investigated mode of inheritance; we examined effects of PKD on longevity; we conducted survival analysis; and we examined l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…From the data generated in this study, it is clear that studbooks are being used to understand population mortality (Duque‐Correa et al, 2022; Metz et al, 2017). Studbooks contain information on cause of death, and lifespan, and can be used to rapidly identify the most common reasons why animals in a population are dying (Flacke et al, 2017). With this knowledge, husbandry interventions can be put in place that reduce species‐specific risks.…”
Section: Discussionmentioning
confidence: 99%
“…From the data generated in this study, it is clear that studbooks are being used to understand population mortality (Duque‐Correa et al, 2022; Metz et al, 2017). Studbooks contain information on cause of death, and lifespan, and can be used to rapidly identify the most common reasons why animals in a population are dying (Flacke et al, 2017). With this knowledge, husbandry interventions can be put in place that reduce species‐specific risks.…”
Section: Discussionmentioning
confidence: 99%
“…The study of FlaCke et al (2016) evaluating causes of deaths described a number of reasons for mortality, some of which could also be linked to inbreeding levels in the population, as inbred animals are more susceptible to pathogens and have higher rates of recessive disease than do non-inbred ones. For example, analysis of survival in polycystic kidney disease in 149 individuals, showed that non-inbred animals had a higher chance of survival to 1 year of age than did inbred pygmy hippos, even though the inbreeding itself did not have a significant effect on occurrence of the studied disease (FlaCke et al 2017).…”
Section: Inbreeding Effectmentioning
confidence: 99%
“…There is little information from the wild, which is mainly due to the species' cryptic behaviour and difficulties accessing their natural habitat. In captivity, individuals suffer from persistent health problems, such as polycystic kidney disease and dental skin and foot problems, which may originate from inadequate diet (Flacke et al, 2017; von Houwald et al, 2007). Pygmy hippos appear to forage mainly at night over a period of about 6 hours (Eltringham, 1999; Mallon et al, 2011; Robinson, 1981).…”
Section: Introductionmentioning
confidence: 99%